177k views
0 votes
Find the equivalent expression by drawing a line from the left column to the right

Find the equivalent expression by drawing a line from the left column to the right-example-1
User TekTimmy
by
4.9k points

1 Answer

5 votes

Answer/Step-by-step explanation:


2(3x - 1) = 2*3x 2*-1 = 6x - 2


(x*y)2 = (xy)2 = 2xy


2(2x - 3) = 2*2x 2*-3 = 4x - 6


3x + 4x + 2 = (3x + 4x) + 2 = 7x + 2


7x - 7 = 7(x) - 7(1) = 7(x - 1)


x(6 + 9) = x(15) = 15x


2 + 9x + 1 + 3x = (9x + 3x) + (2 + 1) = 12x + 3


4(x + 2) + x = 4x + 8 + x = 4x + x + 8 = 5x + 8

User Dollar
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.